Nectary structure of Cotoneaster roseus - Nagy Tóth, Erika; Filep, Rita; Farkas, Ágnes (Acta Biologica Szegediensis, 2011)
Cotoneasters are widely planted as ornamentals, which at the same time can serve as a sources of nectar for honey bees and bumble bees. The present study gives a detailed description of the nectary anatomy of Cotoneaster roseus. The floral nectary is located within the receptacle, with well distinguishable regions of the epidermis, glandular tissue and nectary parenchyma. Modified nectary stomata are at level with or below the epidermis; the glandular cells are arranged in 3 to 4 subepidermal layers; and calcium oxalate crystals are typical in the nectary parenchyma. Data are provided on the size and thickness of the nectar gland, which can be significant factors determining the nectar producing ability of the flowers.